Playing with the past - Champion, Erik (Human-computer interaction series, 2011)
How can we increase awareness and understanding of other cultures using interactive digital visualizations of past civilizations? In order to answer the above question, this book first examines the needs and requirements of virtual travelers and virtual tourists. Is there a market for virtual travel? Erik Champion examines the overall success of current virtual environments, especially the phenomenon of computer